Identifying patient‐centered outcomes for children with cancer and their caregivers when they seek care in the emergency department. Issue 10 (16th July 2019) - Mueller, Emily L.; Cochrane, Anneli R.; Lynch, Dustin O.; Cockrum, Brandon P.; Wiehe, Sarah E.
Abstract: Background: Children with cancer have high utilization of the emergency department (ED), but little is known about which outcomes are most important to them and their caregivers when they seek care in the ED. Procedure: A qualitative evaluation of ED experience for children with cancer and their caregivers was performed using self‐reported interactive toolkits. Eligible participants included children with cancer (ages 11‐19) and caregivers of children with cancer whose child received cancer therapy within the last year and had an ED visit within the last 2 years. Eligible participants received toolkits by mail and received incentives if they completed the toolkit. Toolkits were transcribed, thematically coded, and iteratively analyzed using Nvivo 11.0 software. Results: There were 26 toolkits received—seven by children aged 11‐17 years and 19 by caregivers (11 with children aged 2‐7 years, eight with children aged 11‐17 years). About half were from within 1 h of their treating institution. The most important outcomes to this population included system‐level issues (eg, cleanliness of space, timeliness of evaluation) and oncology‐provider‐ and ED‐provider‐level issues (eg, ability to access port‐a‐caths, quality of communication). Participants also identified outcomes that were within the control of the patient/caregiver, such as improving their sense of preparedness. Conclusion: The important outcomes to children with cancer and their caregivers when they seek care in the ED are distinct from current quality metrics. Future research should focus on the development and validation of a patient‐centered outcomes tool.